THE RELATIONSHIP BETWEEN WORK-FAMILY CONFLICT AND JOB SATISFACTION AMONG FAMILY MEDICINE PHYSICIANS IN SAUDI ARABIA - Alali, Mohammed Jassim, Almustafa, Yassmeen Majid, Alokail, Jawaher Abd Alaziz, (Chelonian Research Foundation, 2022)
Work-family conflict is a prevalent issue among healthcare professionals, particularly physicians, and has been associated with various negative outcomes, including reduced job satisfaction. This study aimed to investigate the relationship between work-family conflict and job satisfaction among family medicine physicians in Saudi Arabia. A cross-sectional survey design was employed, and data were collected from a sample of 250 family medicine physicians working in primary healthcare centers in Riyadh, Saudi Arabia. The survey included the Work-Family Conflict Scale and the Job Satisfaction Survey. Descriptive statistics, Pearson's correlation, and multiple linear regression analyses were conducted to examine the relationships between variables. The results revealed a significant negative correlation between work-family conflict and job satisfaction (r = -0.68, p < 0.001). Multiple linear regression analysis showed that work-family conflict significantly predicted job satisfaction (β = -0.64, p < 0.001), after controlling for demographic variables. The findings highlight the importance of addressing work-family conflict to improve job satisfaction among family medicine physicians in Saudi Arabia. Recommendations for healthcare organizations and policymakers are discussed, including the implementation of family-friendly policies, flexible work arrangements, and support programs for physicians. Keywords: work-family conflict, job satisfaction, family medicine physicians, Saudi Arabia, primary healthcare